If I Could Write This in Fire - Cliff, Michelle (Book collections on Project MUSE., 2008)
Born in a Jamaica still under British rule, the acclaimed and influential writer Michelle Cliff embraced her many identities, shaped by her experiences with the forces of colonialism and oppression: a light-skinned Creole, a lesbian, an immigrant in both England and the United States. In her celebrated novels and short stories, she has probed the intersection of prejudice and oppression with a rare and striking lyricism. In her first book-length collection of nonfiction, Cliff displays the same poetic intensity, interweaving reflections on her life in Jamaica, England, and the United States wi.